Mean-Variance Efficiency and Intertemporal Price for Risk - Johannes Leitner (University of Konstanz, Center of Finance and Econometrics (CoFE), 2000)
In a continuous time, arbitrage free, non-complete market with a zero bond, we find the intertemporal price for risk to equal the standard deviation of the discounted variance opti- mal martingale measure divided by the zero bond price. We show the Hedging Numeraire to equal the Market Portfolio and find the mean-variance efficient portfolios.
urn:nbn:de:bsz:352-opus-6184
Keywords: 330; CAPM; Hedging; Portfolio-Management; Kapitalmarkttheorie; Theorie; Maßzahl